Imaging techniques - Bandello, Francesco; Carnevali, Adriano; Cheung, Gemmy C. M.; Cunha-Vaz, José 1938-; Corvi, Federico; Koh, Adrian Hock Chuan (Basel : Karger, 2018)
The introduction of new imaging methods has revolutionized the management of retinal diseases. Techniques like OCT angiography and fundus autofluorescence imaging have enabled the exploration of new perspectives for understanding the progress of diseases such as age-related macular degeneration (AMD) and diabetic retinopathy. Multimodal imaging of the retina will open new avenues for an integrated diagnostic approach in the future. This publication - like all volumes of the 'ESASO Course Series' - summarizes the essentials of the ESASO education courses. It provides an update for retina specialists and imaging technicians. Residents and trainees will also find it to be useful for learning about new imaging techniques.
La función de los autores fue determinada por el catalogador
Keywords: RETINA -- ENFERMEDADES -- DIAGNÓSTICO POR IMÁGENES; TOMOGRAFÍA DE COHERENCIA OPTICA; ANGIOGRAFÍA POR FLUORESCENCIA